The Public Distrust and Its Impact on the Penetration of Islamic Banking: A Study of the Low Level of Interest in Sharia Financial Products in Indonesia - Arianti Wulan Savitri Wulan; Jati Prihantono Jati (Department of Sharia Economic Law, 2026)
The development of the Islamic banking industry in Indonesia still faces serious challenges, one of which is the low level of public interest in Islamic financial products. This study aims to analyze the relationship between public distrust and public interest in using Islamic banking services, and to explore the factors that influence it. This study uses a descriptive qualitative approach through literature studies and secondary data reviews from financial reports, scientific literature, and national financial literacy surveys. The results of the study indicate that low levels of Islamic financial literacy, negative perceptions of transparency and compliance of Islamic banks, and lack of product innovation are the main causes of low public trust. This low level of trust has a direct impact on the low level of public interest in switching to Islamic financial products. The findings also emphasize the importance of the role of education, strengthening regulations, and marketing strategies based on Islamic values and digitalization to increase public participation.